Sphingosine kinases negatively regulate the expression of matrix metalloproteases (MMP1 and MMP3) and their inhibitor TIMP3 genes via sphingosine 1‐phosphate in extravillous trophoblasts. (22nd March 2021) - Chahar, Kirti R.; Kumar, Vijay; Sharma, Phulwanti K.; Brünnert, Daniela; Kaushik, Vibha; Gehlot, Pragya; Shekhawat, Indu; Kumar, Suman; Sharma, Ajay Kumar; Kumari, Sandhya; Goyal, Pankaj
Abstract: Purpose: Extracellular matrix remodeling is essential for extravillous trophoblast (EVT) cell migration and invasion during placental development and regulated by matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteases (TIMPs). Sphingosine kinases (SPHK1 and SPHK2) synthesize sphingosine‐1‐phosphate (S1P), which works either intracellularly or extracellularly via its receptors S1PR1‐5 in an autocrine or paracrine manner. The role of SPHKs/S1P in regulating the expression of MMPs and TIMPs in EVT is mostly unknown and forms the primary objective of the study. Methods: HTR‐8/SVneo cells were used as a model of EVT. To inhibit the expression of SPHKs, cells were treated with specific inhibitors, SK1‐I and SKI‐II, or gene‐specific siRNAs. The expressions of MMPs and TIMPs were estimated by qPCR. Results: We demonstrated that SPHK1, MMP1‐3, and TIMP1‐3 were highly expressed in HTR‐8/SVneo cells. We found that treatment of cells with SK1‐I, SKI‐II, and knockdown of SPHK1 or SPHK2 increased the expression of MMP1, MMP3, and TIMP3 . The addition of extracellular S1P inhibits the upregulation of MMPs and TIMPs in treated cells. Conclusions: SPHKs negatively regulate the expression of MMP1, MMP3, and TIMP3 . The level of intracellular S1P acts as a negative feedback switch for MMP1, MMP3, and TIMP3 expression in EVT cells. Abstract : The levels of intracellular S1P act as a controlling switch for MMP1, MMP3, and TIMP3 expression in EVT cells suggesting a new role of intracellular S1P in ECM remodeling.